EFEKTIVITAS VARIASI KETEBALAN ARANG AKTIF TEMPURUNG KELAPA DALAM MENYERAP KANDUNGAN LOGAM BERAT TIMBAL (Pb) PADA LARUTAN PESTISIDA MENGANDUNG TIMBAL - Juvita Ayu Puspitaloka; Nur Endah Wahyuningsih; Budiyono Budiyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The pesticide is a mixture of substances that are used to reduce the incidence of plant pests so as to protect agricultural product. This research was conducted to determine the effectiveness of thickness variations of coconut shell activated charcoal in reducing lead levels in dithane pesticide solution. Based on PP No.82 Year 2001 the threshold value for lead (Pb) on agricultural land is 0.03 mg / l. The type of research used is Quasi Experimental with a quasi experiment design with control group design. The independent variable in this study was the variation in thickness of coconut shell activated charcoal with a thickness of 4 cm, 8 cm, 12 cm, 16 cm, and 20 cm. The dependent variable is a decrease in lead levels (Pb) in dithane pesticide solution as much as 8 liters. The statistical test used was the Kruskal-Wallis test (p-value = 0.05). The test results showed that the levels of lead (Pb) in the solution before treatment were 0.235 mg / l and at the control 0.202 mg / l. There is a difference in the decrease in lead levels (Pb) in dithane pesticide solution with variations in thickness of activated coconut shell. The most optimum thickness variation for reducing lead 20 cm thickness with an efficiency of 27,26%. The thickness of activated carbon of coconut shell media not effective in reducing the levels of heavy metal lead in pesticide solutions.